Correlation Between Knowledge and Awareness of Human Papillomavirus Vaccine Among Adolescent Girls in Junior High School - Dwinova, Raras; Samaria, Dora (Universitas Pelita Harapan, 2023)
Cervical cancer is significantly increased by the Human Papillomavirus (HPV). The HPV vaccine can be administered as a primary preventive to stop cervical cancer. Cervical cancer can be prevented most effectively with vaccination. The decision to acquire the HPV vaccine is influenced by factors related to knowledge and awareness of the disease. This study aims to ascertain how adolescent girls’ knowledge and awareness of the HPV vaccine relate to one another. In this study, a cross-sectional approach was utilized. One hundred twenty-eight respondents were selected using a cluster random sampling. This study employed the Knowledge regarding HPV, Cervical Cancer, and HPV Vaccine Questionnaire and Awareness about Cervical Cancer, HPV, and HPV Vaccines Questionnaire, all declared valid and reliable. The Spearman Rank test was performed to analyze the data. According to the results, there was a relationship between knowledge and awareness of the HPV vaccine in adolescent girls (r= 0.554; p-value=0.000). Therefore, teenage girls’ knowledge and awareness of the HPV vaccine were related. It is suggested that health professionals, particularly those working with young girls, should provide easy-to-understand information about the HPV vaccine and cervical cancer.